PENINGKATAN KOMPETENSI GURU BIOLOGI TINGKAT SMA SE-KABUPATEN TOBA MELALUI PELATIHAN POLYMERASE CHAIN REACTION (PCR) DAN ELEKTROFORESIS DNA - Roga Florida Kembaren; Yulisa Lestari; Merry Meryam Martgrita; Berlian Simanjuntak; Chintya Sinar Lumbantoruan; FBA Fitriani; Theodora M Putri; Adrianto Prihartantyo; Juli Yanti Damanik; Andrew Rolas Siagian; Endang Sibarani; Bastian Jose Habeahan; Intan Agustiani Sitorus; Ivana Godelva Br. Sidabutar; Lira Oktarina Zefanya Aruan (Universitas Mataram, 2026)
This community service activity aims to improve the professional competence of biology teachers, particularly in molecular biology. Polymerase Chain Reaction (PCR) and DNA electrophoresis are basic molecular biology techniques that require the integration of learning with practical activities. PCR and DNA electrophoresis practical work requires a very specific laboratory, and schools, especially in the Toba region, do not yet have these facilities. Therefore, the Faculty of Biotechnology at the Del Institute of Technology facilitated PCR and DNA electrophoresis practical work for high school biology teachers in Toba Regency. Through this activity, participants gained experience in integrating learning and practical work, which is expected to improve their competence in delivering material related to molecular biology so that learning takes place effectively and optimally. The training activity began with a preliminary test to evaluate understanding of the material and continued with the provision of basic theory on PCR and DNA electrophoresis. Next, practical activities were carried out in the laboratory through intensive guidance in introducing instruments, performing PCR, DNA electrophoresis stages, and analyzing practical results. The community service activity ended with a final evaluation. From the initial and final evaluation results, there was an average increase of 74.48% for PCR and 71.26% for DNA electrophoresis. This outreach activity had a positive impact on the participants and successfully transferred knowledge to them.